1990
DOI: 10.1172/jci114587
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypernatremia on organic brain osmoles.

Abstract: We studied the effects of varying degrees and durations of hypernatremia on the brain concentrations of organic compounds believed to be important, so-called "idiogenic" osmoles in rats by means of conventional biochemical assays, nuclear magnetic resonance spectroscopy, and high-performance liquid chromatography. There were no changes in the concentrations of these osmoles (specifically myoinositol, sorbitol, betaine, glycerophosphorylcholine [GPCI, phosphocreatine, glutamine, glutamate, and taurine) in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
164
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(175 citation statements)
references
References 23 publications
(28 reference statements)
9
164
0
2
Order By: Relevance
“…The Cho resonance contains contributions from phosphocholine and glycerophosphorylcholine; available evidence suggests that glycerophosphorylcholine, which comprises at least half of the MR-visible peak (Miller et al, 1996), is a cerebral osmolyte (Lien et al, 1990;Videen et al, 1995). Chronic renal failure, for example, associated with a prolonged hyerposmotic state, demonstrates a positive correlation between MRS-derived Cho and serum osmotic pressure (Sasaki et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The Cho resonance contains contributions from phosphocholine and glycerophosphorylcholine; available evidence suggests that glycerophosphorylcholine, which comprises at least half of the MR-visible peak (Miller et al, 1996), is a cerebral osmolyte (Lien et al, 1990;Videen et al, 1995). Chronic renal failure, for example, associated with a prolonged hyerposmotic state, demonstrates a positive correlation between MRS-derived Cho and serum osmotic pressure (Sasaki et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 In response to brain shrinkage induced by hypernatremia, the human brain initiates an adaptive response to form idiogenic osmoles that increase intracellular sodium concentrations and restore lost water. [18][19][20] This phenomenon increases the susceptibility of the brain to cellular edema and hemorrhage. 15,20 Baraton et al reported that changes in serum sodium levels of more than 13 meq l À1 was significantly associated with the development of impaired functional outcomes after adjustment for GA, as well as perinatal and neonatal hospitalization characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…(41) Chronic hypernatremia is associated with increased concentration of organic osmolytes in the brain as a protective mechanism. (6,42) The most important of these osmolytes can be quantified with proton nuclear magnetic resonance (NMR) spectroscopy in the brain of humans in vivo. (43,44) This was suggested to be valuable in guiding the therapy of hypernatremic patients.…”
Section: Resultsmentioning
confidence: 99%